The Influence of Service Quality, Product Quality, Price, and Location on Customer Satisfaction Mediated by Purchase Decisions on Vansha Chicken Meat Slaughter - Alfian Hanafi; Muhamad Imam Syairozi; Abid Muhtarom (Jurnal Multidisiplin Sahombu, 2024)
This study aims to see how influential the variables are, service quality, product quality, price and location on customer satisfaction mediated by the purchase decision, to see which variables are the most dominant with customer satisfaction variables in the slaughter of vansha chicken. This study uses a quantitative method, a sample of 95 respondents by calculating the sample using the slovin formula and the population of this study is customers of the slaughter of vansha chicken meat which is taken within 3 months, the method used in this study is SEM using the PLS test tool. The results of the research on the hypothesis test were that service quality (X1) and product quality (X2) had positive and significant results and while the price variables (X3) and location (X4) had negative and significant results. And for the mediation test of the variables of service quality, product quality, price and location to customer satisfaction mediated by the purchase decision is declared partial mediation.